2018
DOI: 10.1111/eva.12689
|View full text |Cite
|
Sign up to set email alerts
|

Comparing genomic signatures of domestication in two Atlantic salmon (Salmo salar L.) populations with different geographical origins

Abstract: Selective breeding and genetic improvement have left detectable signatures on the genomes of domestic species. The elucidation of such signatures is fundamental for detecting genomic regions of biological relevance to domestication and improving management practices. In aquaculture, domestication was carried out independently in different locations worldwide, which provides opportunities to study the parallel effects of domestication on the genome of individuals that have been selected for similar traits. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 119 publications
11
56
1
Order By: Relevance
“…An outlier was found in transient receptor potential cation channel subfamily M member 6 , and interestingly member 3-like from the same cation channel subfamily member was found to be a parallel domestication outlier in both Scottish and Canadian domestic Atlantic salmon (López et al, 2019). Several other genes identified here have also been identified as being involved in domestication processes, such as mitochondrial uncoupling protein 2 , which has undergone loss of function mutations in pig ( Sus scrofa domesticus ) domestication and potentially has led to the reduction of cold tolerance of pigs (Berg et al, 2006) as well as being found to be an outlier in domestic dogs Canis lupus familiaris (Udagawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An outlier was found in transient receptor potential cation channel subfamily M member 6 , and interestingly member 3-like from the same cation channel subfamily member was found to be a parallel domestication outlier in both Scottish and Canadian domestic Atlantic salmon (López et al, 2019). Several other genes identified here have also been identified as being involved in domestication processes, such as mitochondrial uncoupling protein 2 , which has undergone loss of function mutations in pig ( Sus scrofa domesticus ) domestication and potentially has led to the reduction of cold tolerance of pigs (Berg et al, 2006) as well as being found to be an outlier in domestic dogs Canis lupus familiaris (Udagawa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…2018c; López et al . ). Rainbow trout and coho salmon Chilean breeding populations were established based on improved germplasm introduced from multiple origins and the west coast of North America (e.g.…”
Section: Structure Of the Chilean Salmon And Trout Egg Marketmentioning
confidence: 97%
“…In Chile, commercial breeding programmes started being established in the late 1990s. Atlantic salmon breeding populations were created mainly based on improved germsplasm from Norwegian origin; however, North American and Scottish material was also introduced for the same purposes (Barr ıa et al 2018c;L opez et al 2018). Rainbow trout and coho salmon Chilean breeding populations were established based on improved germplasm introduced from multiple origins and the west coast of North America (e.g.…”
Section: Structure Of the Chilean Salmon And Trout Egg Marketmentioning
confidence: 99%
“…2015; L iu et al . 2016; López et al . 2018) exploration of selection signatures in additional populations will illuminate how genetic variation among the different strains, adapted to different culture conditions, across hemispheres has not been assessed yet.…”
Section: Introductionmentioning
confidence: 99%